Designing a model and tool for measuring the literacy of primary school principals: Grounded theory - Samad Borzoian Shirvan; afshin norouzi elmi; Morteza Taheri (Shahid Chamran University of Ahvaz, 2022)
Introduction:Economic challenges (recession, inflation, etc.) always affect the quality and quantity of education and on the other hand, the quality of any educational system depends on the quality of the administrators of that system. School principals should be able to meet the challenges of their school. Also, improve the quality of education in their schools. Financial literacy is a tool that can be a powerful arm of school principals in solving school financial challenges. The purpose of this study is to provide a model and tool for measuring the financial literacy of primary school principals.Method:The method used in this research is Grounded theory. Using purposive sampling method, 8 university professors in the field of education economics and 2 school principals were selected. Data were collected using semi-structured interviews. Then the data were coded by the three-step method in Grounded theory.Results:Finally, principals 'financial literacy was explained and the causal factors, contexts, strategies, intervention factors and consequences of school principals' financial literacy were identified. Then, according to the identified factors, the model and form of measuring the financial literacy of school principals was presented.Discussion:School principals must have a set of competencies and skills to maintain the quality and improve the conditions of the school under their management. Financial literacy is one of these competencies that empowers principals in solving the financial challenges of schools. Assessing and determining the current situation School principals' financial literacy needs a model and tools. School principals' financial literacy assessment model explains the various dimensions and angles of school principals' financial literacy. Educators and founders of private schools. Policymakers and decision-makers in the education system should pay special attention to the financial literacy of school principals, and education district administrators should consider financial literacy in the appointment and selection of school principals